Pemodelan Sistem untuk Produksi Roti Gepeng pada Roti Gepeng ZB (Zebra Brother) Balikpapan Menggunakan Metode Sistem Dinamis - Hertadi, Christopher Davito Prabandewa; Saputro, Keysha Lovelly Adhara; Yaqin, Alvin Muhammad 'Ainul (Study Program of Industrial Engineering, Udayana University, 2025)
Bread is a practical source of carbohydrates and is popular among people of all ages, from children to adults. The flatbread factory,